Analisis Analysis Of The Implementation Of The Village Medium-Term Development Plan (RPJMDES) In Lenggahsari Village, Cabangbungin District, Bekasi Regency - Jovanca Putri Gervia Tahupiah; Evi Priyanti (Journal of Government Science Studies, 2026)
This article examines the implementation of the Village Medium-Term Development Plan (RPJMDes) in Lenggahsari Village, Cabangbungin District, Bekasi Regency. The aim of this study is to analyze the effectiveness of RPJMDes implementation using a policy implementation model and a transformational leadership approach. The research adopts a qualitative approach, with data collection through in-depth interviews with village stakeholders and document analysis. The findings indicate that despite efforts by the village government to improve performance, significant challenges remain, such as limited capacity of village officials, weak oversight systems, and low levels of community participation. This study contributes theoretically by integrating the policy implementation model and transformational leadership in the context of village governance. Practically, it suggests enhancing human resource capacity, strengthening oversight systems, and increasing community involvement as solutions to improve the effectiveness of RPJMDes implementation. The implications of this research highlight the need for more adaptive policies and synergy between the government, communities, and other stakeholders to create a village government that is transparent, accountable, and responsive to community needs.